Factors Involved in the Persistence of a Shiga Toxin-Producing Escherichia coli O157:H7 Strain in Bovine Feces and Gastro-Intestinal Content - Segura, Audrey; Auffret, Pauline; Bibbal, Delphine; Bertoni, Marine; Durand, Alexandra; Jubelin, Grégory; Kérourédan, Monique; Brugère, Hubert; Bertin, Yolande; Forano, Evelyne (Frontiers in Microbiology, 2018)
Healthy cattle are the primary reservoir for O157:H7 Shiga toxin-producing E. coli responsible for human food-borne infections. Because farm environment acts as a source of cattle contamination, it is important to better understand the factors controlling the persistence of E. coli O157:H7 outside the bovine gut. The E. coli O157:H7 strain MC2, identified as a persistent strain in French farms, possessed the characteristics required to cause human infections and genetic markers associated with clinical O157:H7 isolates. Therefore, the capacity of E. coli MC2 to survive during its transit through the bovine gastro-intestinal tract (GIT) and to respond to stresses potentially encountered in extra-intestinal environments was analyzed. E. coli MC2 survived in rumen fluids, grew in the content of posterior digestive compartments and survived in bovine feces at 15°C predicting a successful transit of the bacteria along the bovine GIT and its persistence outside the bovine intestine. E. coli MC2 possessed the genetic information encoding fourteen adherence systems including adhesins with properties related to colonization of the bovine intestine (F9 fimbriae, EhaA and EspP autotransporters, HCP pilus, FdeC adhesin) reflecting the capacity of the bacteria to colonize different segments of the bovine GIT. E. coli MC2 was also a strong biofilm producer when incubated in fecal samples at low temperature and had a greater ability to form biofilms than the bovine commensal E. coli strain BG1. Furthermore, in contrast to BG1, E. coli MC2 responded to temperature stresses by inducing the genes cspA and htrA during its survival in bovine feces at 15°C. E. coli MC2 also activated genes that are part of the GhoT/GhoS, HicA/HicB and EcnB/EcnA toxin/antitoxin systems involved in the response of E. coli to nutrient starvation and chemical stresses. In summary, the large number of colonization factors known to bind to intestinal epithelium and to biotic or abiotic surfaces, the capacity to produce biofilms and to activate stress fitness genes in bovine feces could explain the persistence of E. coli MC2 in the farm environment.